TWO-WAREHOUSE INVENTORY MODEL FOR MAXIMUM LIFETIME ITEMS CONSIDERING CAPITAL REDUNDANCY UNDER ADVANCE PAYMENT - Aliyu, Zaharaddeen H.; Adamu, Zainab; Malumfashi, Amina A.; Mukhtar, Nafisat L. (FUDMA Journal of Sciences, 2025)
Maintaining inventory of deteriorating items is an enormous task owing to their nature. These items do not only deteriorate but also expire with time. This prompt investigating both instantaneously and non- instantaneously deteriorating items that have maximum lifetime under different conditions due to their complexity. The models for those items have been developed under different promotional tools such as trade credit and discounts. However, they are yet to be explored under advance payment scheme in a capacity-constrained environment. In this work, an inventory model has been developed considering maximum lifetime items under two-warehouse. The dispatching policy adopted is First-in First-out (FIFO) due to the fact that freshness of items is considered more important than economic reasons. Advance payment was incorporated into the model to make it more practical especially in developing nations where competition to get the order from the supplier, when placed by the retailer, is high. With the help of several realistic cases, cost functions were obtained and numerical example is given as an illustration of the model. The result showed that the goods in the rented warehouse (RW) finishes at 0.746 while the replenishment cycle ends at 0.956 indicating that the retailer incurred a larger holding costs.  From the sensitivity analysis, it was found that the longer the lifetime of an item, the smaller the total cost incurred by the retailer indicating that it is better for the retailer to order items with bigger lifetime from the managerial point of view.
Keywords: First-in-First-out; Maximum lifetime items; Two-warehouse; Advance payment